Progress of chromosome engineering mediated by asymmetric somatic hybridization - Xia, Guangmin (Journal of genetics and genomics, 2009)
Plant somatic hybridization has progressed steadily over the past 35 years. Many hybrid plants have been generated from fusion combinations of different phylogenetic species, some of which have been utilized in crop breeding programs. Among them, asymmetric hybrid, which usually contains a fraction of alien genome, has received more attention because of its importance in crop improvement. However, few studies have dealt with the heredity of the genome of somatic hybrid for a long time, which has limited the progress of this approach. Over recent ten years, along with the development of an effective cytogenetical tool ＂in situ hybridization （ISH）＂, asymmetric fusion of common wheat （Triticum aestivum L.） with different grasses or cereals has been greatly developed. Genetics, genomes, functional genes and agricultt, ral traits of wheat asymmetric hybrids have been subject to systematic investigations using gene cloning, genomic in situ hybridization （GISH） and molecular makers. The future goal is to fully elucidate the functional relationships among improved agronomic traits, the genes and underlying molecular mechanisms, and the genome dynamics of somatic introgression lines. This will accelerate the development of elite germplasms via somatic hybridization and the application of these materials in the molecular improvement of crop plants.